3D numerical simulation of consolidation induced in soft ground by EPB technology and lining defects. (December 2020) - Ochmański, Maciej; Spacagna, Rose Line; Modoni, Giuseppe
Abstract: This paper analyses with a sophisticated numerical model the long-term phenomenology induced by Earth Pressure Balance tunnelling in compressible, low permeability soils. The complex soil-structure interaction determined by the EPB technology is analysed with a three-dimensional model that closely reproduces the sequence of face pressurisation, excavation, lining installation and tail grout injection and simulates the hydro-mechanical soil coupled response with a non-linear, irreversible, anisotropic hypoplastic model. After validation on a documented case study taken from literature, the model has been applied to a real example, MRTA Project in Bangkok. The study reveals that short and long-term settlements induced by tunnelling cannot be decoupled, being both governed by the fluid-soil-lining interaction and resulting from the time dependent stress transfer among the different elements. In this scenario over pressurising face and tail void reduces the immediate soil relaxation at the expenses of increasing the long-term settlements. Local or global defects have then been hypothesized on the lining waterproofness considering different initial groundwater conditions, soil permeability models and sets of EPB operative parameters. While concentrated lining defects play a negligible role, extensive imperfection noticeably increases settlements, volume loss and bending moments on the lining, with the same function of the relative soil-lining permeability.